2015
DOI: 10.1039/c4ta06820c
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the H2/CO2upper bound: one-step crystallization and separation of nano-sized ZIF-11 by centrifugation and its application in mixed matrix membranes

Abstract: ARTICLEThis journal is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 45 publications
4
70
0
2
Order By: Relevance
“…This points out not only the relevance of the porous texture, as detailed above, but also the morphology (which can have an effect in the concentration of defects that may act as adsorption sites) and chemical composition of the solid, which have a strong influence in the adsorption strength. This was also observed for zeolite imidazolate framework (ZIF) samples in which the final morphology, was strongly influenced by the preparation method . In this particular paper, the preparation of ZIF‐11 with very small crystal size resulted in an impoverishment in their adsorption performance.…”
Section: Hydrogen Storage In Porous Materials: State Of the Artmentioning
confidence: 67%
“…This points out not only the relevance of the porous texture, as detailed above, but also the morphology (which can have an effect in the concentration of defects that may act as adsorption sites) and chemical composition of the solid, which have a strong influence in the adsorption strength. This was also observed for zeolite imidazolate framework (ZIF) samples in which the final morphology, was strongly influenced by the preparation method . In this particular paper, the preparation of ZIF‐11 with very small crystal size resulted in an impoverishment in their adsorption performance.…”
Section: Hydrogen Storage In Porous Materials: State Of the Artmentioning
confidence: 67%
“…[6][7][8] In any event, works from Ge et al 9 and Severance et al 10 where Al-rich zeolites were grown on polymeric surfaces were reported. Both MMMs (mixed-matrix membranes) and supported MOFpolymer membranes have been developed for gas separation, [11][12][13] liquid phase pervaporation 14 and nanofiltration 15 processes. Recently some authors have used hollow fiber (HF) shaped polymers as membrane supports for MOF continuous layers.…”
Section: High Selectivity Zif-93 Hollow Fiber Membranes For Gas Separmentioning
confidence: 99%
“…The bands occurring at around 530–400 cm −1 were characteristic of ZnO molecules and were observed clearly in the pure ZIF‐11 spectra (Fig. b) . The peak at 427 cm −1 corresponded to Zn–N stretching and became more visible as loading increased at 10, 20, 30 wt.% loadings, and this was a supplementary proof for the existence of intact ZIF‐11 particles in MMMs.…”
Section: Resultsmentioning
confidence: 77%
“…The ZIF‐11 crystals displayed characteristic absorption bands at 3088, 3057, 3032 cm −1 (=C–H stretching of aromatics), and 1611, 1465 cm −1 (C–C stretching in the aromatic ring). The bands occurring at around 530–400 cm −1 were fingerprints of ZnO . In particular, the band at 427 cm −1 corresponded to Zn–N stretching.…”
Section: Resultsmentioning
confidence: 98%